Diameter growth rates in tropical dry forests: contributions to the sustainable management of forests in the Bolivian Cerrado biogeographical province - López, Lidio; Villalba, Ricardo; Peña-Claros, Marielos (Bosque (Valdivia), 2017)
Growth ring variations were used to provide the rates in diameter growth for seven tree species in the Bolivian Cerrado biogeographical province. Ten to 50 trees were measured per species. Ring width measurements provided accurate data on the rates of tree growth. Variations in growth rates were determined among species and among sites for the same species over a common period of 100 years. Diametric increases range from 0.43 to 0.56 cm year-1 in Chiquitano biogeographical district. For species in Guarayos district, diametric increments range from 0.51 to 1.06 cm year-1. For Centrolobium microchaete growing in both districts, the annual diametric increments oscillate between 0.35 to 0.40 cm year-1 and 0.55 to 0.65 cm year-1 in Chiquitano and Guarayos districts, respectively. Diametric increases in Chiquitano district were not significantly different among sites, whereas in Guarayos district, annual increases differ among species and from the same species growing in Chiquitano district. Observed diameter growth rates indicate that diametrical increments are generally slower than commonly assumed, with considerable variation among species and between districts. Therefore, the idea of applying similar rules for the management of different species across different sites without considering actual growth rates is not recommended, with long-term consequences for the sustainability of forests at the tropical dry Bolivian Cerrado.